Augustine’s view of Manichaean almsgiving and almsgiving by the Manichaean community at Kellis - Franzmann, Majella (AOSIS OpenJournals, 2013)
Taking its point of departure from Augustine’s criticism of Manichaean practices with food and drink that appear to disregard the New Testament injunction to give to the poor, or to those who are hungry and thirsty, this article investigates the probability that this was indeed Manichaean practice, by interrogating Manichaean texts and clues about Manichaean practice contained in the personal letters from 4th century CE Roman Kellis in Egypt. A further consideration of types of exclusive communities and their behaviour, or exclusive behaviour at various times from groups that are generally characterised as inclusive, leads to the proposal that Manichaean exclusivity was based firmly on an underlying theology and narrative myth of cosmic salvation that fixed an unalterable Manichaean community practice, carried out in a wide range of geographical locations and historical times.